THE AHP APPROACH FOR DETERMINING E-LEARNING PLATFORM IN UNIVERSITY - Jatiningrum, Wandhansari Sekar; Utami, Sri Nastiti Andayani Sesanti Retno; Zalfa, Dhia; Syafril, Muhammad; Wachid, Nur (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2022)
Physical distancing policy as the response to pandemic covid-19 has forced the educational institutes to provide online learning for the students. The students and lecturer have to adapt to using online platforms to continue the learning activities. An E-learning platform is needed for distance learning. This research aims to analyze the preference of e-learning platforms among Google Classroom, Youtube, Whatsapp, and Zoom for students in a private university in Yogyakarta, Indonesia, using the Analytical Hierarchy Process approach. Several criteria are formulated for determining the e-learning platform based on the students’ common difficulties during online-based learning, namely service of platform, learning comprehension, internet usage, and network strength. The result shows that learning comprehension has the highest weight (0.363), followed by network strength (0.258), internet usage (0.230), and platform service (0.149). Learning comprehension has become the most important criterion that students consider on selecting an e-learning platform. The final result from the Analytical Hierarchy Process approach proposes the best alternative e-learning platform for students based on the previous criteria. Based on the research, Whatsapp is an e-learning platform with the highest weight of 0.359. Therefore, it is determined for recommendation as to the most suitable e-learning platform for students. It has a high local weight based on each criterion considered in selecting an e-learning platform. The result of this study is expected to be input for lecturers and education institutions to evaluate the platforms they use and e-learning processes.